DESIGN, CONSTRUCTION AND TESTING OF LOW SPEED WIND TUNNEL WITH ITS MEASUREMENT AND INSPECTION DEVICES (Journal of Engineering, 2011)
A low speed open circuit wind tunnel has been designed, manufactured and constructed at theMechanical Engineering Department at Baghdad University - College of Engineering. The work is one ofthe pioneer projects adapted by the R & D Office at the Iraqi MOHESR. The present paper describes thefirst part of the work; that is the design calculations, simulation and construction. It will be followed by asecond part that describes testing and calibration of the tunnel. The proposed wind tunnel has a testsection with cross sectional area of (0.7 x 0.7 m2) and length of (1.5 m). The maximum speed is about (70m/s) with empty test section. The contraction ratio is (8.16). Three screens are used to minimize flowdisturbances in the test section. The design philosophy is discussed and methods for wind tunnelcalculation are outlined. Simulation of wind tunnel using ANSYS shows no separation of flow alongwind tunnel. Construction steps are also included in present work.